Analisis Framing Media Online Hidayatullah Berita Pro Kontra RUU P-KS Periode 25-29 September 2019 - Arning Susilawati; Edelweis Putri Prima (LPPM Stikosa-AWS, 2022)
The issue of the Draft Law on the Elimination of Sexual Violence (RUU P-KS) was hot again when Bambang Soesatyo (Chairman of the 2014-2019 DPR) stated that the bill would still contain pros and cons. The attitude of the mainstream media tends to show the side of why the P-KS Bill deserves to be passed. Meanwhile, the Islamic media strongly reject the ratification of the bill because it is not in accordance with the norms and religions that apply in Indonesia. Hidayatullah.com as a media based on Islam, of course, will display the news point of view as the ideology of the media. This study aims to determine the pros and cons of the P-KS Bill in the Daring Hidayatullah.com media for the period 25-29 September 2019. The analytical method used is Framing Zhongdang Pan and Gerald M. Kosicki, by looking at the four elements, namely syntax (how to) . compiling fact reports), scripts (how to report facts), thematic (how to write news), and rhetorical (how journalists write facts) on news with the discussion of the P-KS Bill on Hidayatullah.com. The results of research from Hidayatullah.com show an attitude towards the 2014-2019 DPR RI plan to ratify the P-KS Bill. Hidayatullah.com has also met the requirements for completeness of news (5W+1H), but has not met the requirements of what, who, and why. On the theme, Hidayatullah.com is related to the reasons or parties who reject the ratification of the P-KS Bill. In fact, Hidayatullah.com uses the image